Perlindungan Hukum Bagi Pekerja yang Terkena Pemutusan Hubungan Kerja Akibat Resesi Ekonomi - Al Diva Zain Farras Saputra; Suraji Suraji (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to examine the legal protection of workers' rights who are terminated due to economic recession and to analyze the use of economic recession as a valid reason for termination of employment. This is a normative legal research that uses a statutory approach and a conceptual approach. The research relies on primary legal materials such as the 1945 Constitution of the Republic of Indonesia, the Civil Code, Law Number 13 of 2003 concerning Manpower, and Law Number 11 of 2020 concerning Job Creation, as well as secondary legal materials including books, journals, and scholarly articles. The results of the research show that: 1) an economic recession can be considered a valid reason for termination of employment within a company, as it may fall under the category of force majeure, provided that the company still respects the employment agreement and principles of fairness; and 2) legal protection for workers who are laid off due to an economic recession is divided into two forms: internal legal protection (based on the contents of the employment agreement) and external legal protection (based on statutory provisions). In this regard, workers still have the right to receive severance pay, long service pay, and compensation for entitlements.